Influence of Annealing Temperature on Berthelot-Type Hopping Conduction Mechanism in Carbon-Nickel Composite Films. (May 2016) - Dalouji, V.; Elahi, S. M.; Ghaderi, A.; Solaymani, S.
Abstract : Electrical conductivity of carbon-nickel composite films annealed at temperatures 300, 500 and 800°C is studied over a temperature range of 50–300 K. While the conductivity data above room temperature show extended state conduction, lowering the temperature from 150 to 50 K leads to the Berthelot-type conduction mechanism. It can be seen that the films annealed at 500°C have the maximum conductivity. The extent of the carrier wave function at 500°C has the minima 2.87 × 10 −7 cm and 2.45 × 10 −7 cm in octahedral-metal stretching vibrations and intrinsic stretching vibrations of the metal at the tetrahedral site, respectively. The average distances between two vibration octahedral and tetrahedral sites at 500°C also have the minima 1.13 × 10 −7 cm and 0.97 × 10 −7 cm, respectively. The Berthelot temperature for films annealed at 800°C has the minimum of 94.3 K.